Female soccer periodization on anaerobic power/capacity - Purdom, T. M.; Levers, K. S.; Ryan, G. A.; Brown, L.; Giles, J.; McPherson, C. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to observe changes in anaerobic power and capacity (resistance to fatigue) over an annual training cycle (ATC) in 14 Division I female soccer athletes (19.4 ± 1.0 years, 60.8 ± 5.4 kg, 164.9 ± 6.2 cm, 19.5 ± 3.2% body fat, and 48.9 ± 3.9 kg fat free mass). All subjects were evaluated across the ATC at 5 testing blocks (B1-B5) representing seasonal transitions: postcompetition I (B1), prespring (B2), postspring training (B3), precompetition (B4), and postcompetition II (B5) using 3 tests: countermovement vertical jump to measure peak vertical power (PVP), 40-yard sprint to measure peak horizontal power (PHP), and 35-m running anaerobic sprint test to measure anaerobic capacity via fatigue index (FI). Repeated measures analysis of variance was used with the Bonferroni post hoc test when relevant along with Cohen's d to evaluate effect size. Data are represented as mean ± SD; significance set to p < 0.05. Significant performance increases were observed from postseason I to spring season training (B1-B3) in PVP (6.61 ± 3.18 and 7.71 ± 3.20; p < 0.01, d = 1.12) while changes occurred from prespring season to postspring season (B2-B3) in PVP (6.84 ± 3.15 and 7.71 ± 3.20; p = 0.03, d = 0.93) and PHP (6.65 ± 0.97 and 7.55 ± 1.26; p < 0.01, d = 1.06) with no change in body composition. No other significant changes were observed across the ATC (p > 0.05). Increases in PHP and PVP occurred with directed training after B3 and then declined remaining so across the competitive season. Peak horizontal power and PVP may be more sensitive to coaching style and seasonal transition compared with FI and body composition changes.